"It May Be a Luxury, but Not a Problem": A Mixed Methods Study of Teachers' Attitudes towards the Educational Needs of Gifted Students in Norway - Gila Hammer Furnes; Gunnvi Sæle Jokstad (MDPI AG, 2023)
This study aims to investigate Norwegian primary teachers' attitudes towards gifted students and gifted education and discuss their potential impact on their pedagogical practices. In Norway, gifted education is a relatively non-existent phenomenon, and this research field has been scarcely explored in the Norwegian context and teacher education. The Official Norwegian Report NOU 2016:14 highlights a reluctance among Norwegian teachers to cater to gifted students, indicates a lack of training for teachers in identifying and differentiating gifted education, and points out a need for more research within the Norwegian context. In an earlier study, we showed that Norwegian teachers reported having little formal or non-formal education on the theme of gifted education and that few were aware of the abovementioned report. This study aims to investigate Norwegian primary teachers' attitudes towards gifted students and gifted education and discuss their potential impact on their pedagogical practices. Data in the study are collected through an online mixed methods survey in a small municipality in Norway. An interesting finding is that culture significantly influences teachers' attitudes towards gifted education. We argue that teachers' attitudes should be more informed by evidence-based practice and less by culture, as it can impact gifted students' access to equal and adapted education.